Record‐High Superconductivity in Niobium–Titanium Alloy. Issue 11 (7th January 2019) - Guo, Jing; Lin, Gongchang; Cai, Shu; Xi, Chuanying; Zhang, Changjin; Sun, Wanshuo; Wang, Qiuliang; Yang, Ke; Li, Aiguo; Wu, Qi; Zhang, Yuheng; Xiang, Tao; et al.
Abstract: The extraordinary superconductivity has been observed in a pressurized commercial niobium–titanium alloy. Its zero‐resistance superconductivity persists from ambient pressure to the pressure as high as 261.7 GPa, a record‐high pressure up to which a known superconducting state can continuously survive. Remarkably, at such an ultra‐high pressure, although the ambient pressure volume is shrunk by 45% without structural phase transition, the superconducting transition temperature ( T C ) increases to ≈19.1 K from ≈9.6 K, and the critical magnetic field ( H C2 ) at 1.8 K has been enhanced to 19 T from 15.4 T. These results set new records for both the T C and the H C2 among all the known alloy superconductors composed of only transition metal elements. The remarkable high‐pressure superconducting properties observed in the niobium–titanium alloy not only expand the knowledge on this important commercial superconductor but also are helpful for a better understanding on the superconducting mechanism. Abstract : An extraordinary robustness of superconductivity against pressure is found in the commercial niobium–titanium superconductor. Its zero‐resistance superconductivity persists from ambient pressure to 261.7 GPa, a record‐high pressure to which a known superconducting state can survive. At such high pressure, the volume is shrunk by ≈45% without structural phase transition. These results expand the knowledge on this important superconductor.